Manajemen Keuangan Desa melalui Inovasi Electronic Village Budgeting (Studi pada Badan Pemberdayaan Masyarakat dan Pemerintahan Desa Kabupaten Banyuwangi) - Nur Pratiwi, Ratih (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2016)
The need for innovation in public sector is an urgent thing because of various dynamics of public problems that appears and demands for a quick solution. One of the problems that frequently appeared in the management of village government was related to the undisciplined village financial management system. Therefore, the government of Banyuwangi Regency released an innovative program named Electronic Village Budgeting (EVB). Electronic Village Budgeting (EVB) is a system of information technology application that is based on a website about village financial management. The result of the study showed that village financial management at first was conducted manually but at the present time it has become an online-based system using an integrated application. Finally, it is expected to be able to minimalize the village budget misuse by applying this application.